The role of contemporary digital tools and technologies in COVID‐19 crisis: An exploratory analysis. Issue 6 (6th October 2021) - Subramanian, Malliga; Shanmuga Vadivel, Kogilavani; Hatamleh, Wesam Atef; Alnuaim, Abeer Ali; Abdelhady, Mohamed; V E, Sathishkumar
Abstract: Following the COVID‐19 pandemic, there has been an increase in interest in using digital resources to contain pandemics. To avoid, detect, monitor, regulate, track, and manage diseases, predict outbreaks and conduct data analysis and decision‐making processes, a variety of digital technologies are used, ranging from artificial intelligence (AI)‐powered machine learning (ML) or deep learning (DL) focused applications to blockchain technology and big data analytics enabled by cloud computing and the internet of things (IoT). In this paper, we look at how emerging technologies such as the IoT and sensors, AI, ML, DL, blockchain, augmented reality, virtual reality, cloud computing, big data, robots and drones, intelligent mobile apps, and 5G are advancing health care and paving the way to combat the COVID‐19 pandemic. The aim of this research is to look at possible technologies, processes, and tools for addressing COVID‐19 issues such as pre‐screening, early detection, monitoring infected/quarantined individuals, forecasting future infection rates, and more. We also look at the research possibilities that have arisen as a result of the use of emerging technology to handle the COVID‐19 crisis.